Detection of Leptospira sp. Bacteria and Factors Related to the Incidence of Leptospirosis in Semarang City - Diyana, Sutra; Sutiningsih, Dwi; Adi, Mateus Sakundarno; Hitipeuw, Derico (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: The Case Fatality Rate (CFR) of Leptospirosis in Semarang City has shown a tendency to increase from 2019 to 2022. In 2022, there were 30 cases reported, with 8 deaths (CFR 27%). The purpose of this study was to detect Leptospira sp. bacteria in rats and analyze the risk factors for leptospirosis in Semarang City.Methods: This study employed an observational approach with a Case-Control Study design. The research was conducted in Semarang City from November to December 2023. Non-random sampling techniques were used, specifically the total sampling method, resulting in a sample size of 45 case groups and 45 control groups. Bivariate analysis was performed using the Chi-square test, with a significance level set at <0.05.Results: Based on the Chi-Square test results, the following variables were found to be associated with the incidence of leptospirosis in Semarang City: the presence of rats (p<0.0001), the presence of Leptospira sp. bacteria (p<0.0001), house conditions (p=0.260), sewer condition (p<0.0001), presence of pets (p=0.001), condition of landfills (p=0.001), presence of vegetation (p=0.005), temperature (p=0.299), humidity (p=0.495), lighting (p=0.023), history of wounds (p=0.001), and knowledge level (p=0.025).Conclusion: The risk factors for leptospirosis in Semarang City include the presence of rats, the presence of Leptospira sp. bacteria, sewer conditions, the presence of pets, conditions of landfills, the presence of vegetation, lighting, history of injury, and level of knowledge.